MRSA Infection in the Thigh Muscle Leads to Systemic Disease, Strong Inflammation, and Loss of Human Monocytes in Humanized Mice - Hung, Sophia; Dreher, Liane; Diessner, Joachim; Schwarz, Stefan; Ohlsen, Knut; Hertlein, Tobias (Frontiers in Immunology, 2022)
MRSA (Methicillin-resistant Staphylococcus aureus) is the second-leading cause of deaths by antibiotic-resistant bacteria globally, with more than 100,000 attributable deaths annually. Despite the high urgency to develop a vaccine to control this pathogen, all clinical trials with pre-clinically effective candidates failed so far. The recent development of “humanized” mice might help to edge the pre-clinical evaluation closer to the clinical situation and thus to close this gap. We infected humanized NSG mice (huNSG: (NOD)-scid IL2Rnull mice engrafted with human CD34+ hematopoietic stem cells) locally with S. aureus USA300 LAC* lux into the thigh muscle in order to investigate the human immune response to acute and chronic infection. These mice proved not only to be more susceptible to MRSA infection than wild-type or “murinized” mice, but displayed furthermore inferior survival and signs of systemic infection in an otherwise localized infection model. The rate of humanization correlated directly with the severity of disease and survival of the mice. Human and murine cytokine levels in blood and at the primary site of infection were strongly elevated in huNSG mice compared to all control groups. And importantly, differences in human and murine immune cell lineages surfaced during the infection, with human monocyte and B cell numbers in blood and bone marrow being significantly reduced at the later time point of infection. This was particularly notably since murine monocytes behaved conversely, namely by increased cell numbers. This study demonstrates significant differences in the in vivo behavior of human and murine cells towards S. aureus infection, which might help to sharpen the translational power of pre-clinical models for future therapeutic approaches.